The spatial politics of land policy reform in Myanmar and Laos - Kenney-Lazar, M.; Suhardiman, Diana; Hunt, G. (Informa UK Limited, 2023)
Land policy reform has dominated the development agenda across the Global South over the past two decades. In contrast with earlier distributive land reforms, contemporary policies reflect an amalgamation of neoliberal, state territorial, and social justice agendas. This paper demonstrates how land policy changes reflect the spatially extensive and multi-scalar politics of land contestation and control, employing the cases of Myanmar and Laos. Myanmar’s short-lived democratic transition enabled civil society actors to exert uneven influence on policy reform. In contrast, communist party and state dominance in Laos has constrained, although not wholly obstructed, policy intervention by non-governmental groups.